Navies in multipolar worlds
1 online resource (xx, 256 pages)
Keywords: "This volume looks at how navies in previous eras of multipolarity grappled with the challenges of preparing for great-power conflicts. The book follows the theme of multipolarity by analysing a wide range of historical and geographical case studies, thereby maintaining the focus of both its historical analysis and its policy implications. It begins by looking at the evolution of French naval policy from Louis XIV through to the end of the nineteenth century. It then examines how the British responded to multipolar threat environments, convoys, the challenges of demobilization, and the persistence of British naval power in the interwar period. There are also contributions regarding Japan's turn away from the sea, the Italian navy, and multipolarity in the Arctic. This volume also addresses the regional and global distribution of forces; trade and communication protection; arms races; the emergence of naval challengers; fleet design; logistics; technology; civil-naval relations; and grand strategy, past, present, and future. This book will be of much interest to students of naval history, strategic studies and international relations history"--